The conventional autonomic tests have still a role in differentiating multiple system atrophy from Parkinson disease?. Issue 1 (January 2019) - Devigili, G.; Rinaldo, S.; Elia, A.; Romito, L.; Soliveri, P.; Eleopra, R.
Abstract : The differentiation of MSA with predominant parkinsonism (MSA-P) from Parkinson disease (PD) or other parkinsonism disorders may be challenging in early stages of the disease. Dysautonomia may be present both in MSA-P and in PD. This study aims to evaluate the presence and features of autonomic test alteration in a cohort of unselected MSA-P and PD with dysautonomia. We enrolled 52 consecutive patients into a 5-months prospective observational study. All patients performed clinical scales (UPDRS), the Orthostatic Hypotension Questionnarie (OHT), a battery of cardiovascular autonomic tests (deep breathing, standing up, 10 min head-up tilt, Valsalva maneuver, handgrip test), and the sympathetic skin responses (SSR) recording at hands and feet, after electrical, acoustic and endogenous stimuli. 23 patients with PD and 27 with MSA were investigated, the two groups were age, sex and disease duration matched. In MSA-P we found abnormal heart rate variability compared with PD (p = 0.02), while OH did not differ. All MSA-P patients showed late-OH during Tilt Test. SSR was abnormal in 18 MSA – P patients and none of PD.